Rubia Gallega x Nelore crossbred cattle improve beef tenderness through changes in protein abundance and gene expression - Ferrinho, Adrielle M.; de Moura, Gabriella Vespe; Martins, Taiane da Silva; Muñoz, Julian; Mueller, Lenise F.; Garbossa, Pollyana Leite Matioli; de Amorim, Tamyres Rodrigues; Gemelli, Jéssica Luana; Fuzikawa, Ingrid Harumi de Souza; Prado, Cibele; da Silveira, Juliano Coelho; Poleti, Mirele D.; et al. (Elsevier, 2021)
The objective was to evaluate meat quality of Rubia Gallega x Nelore (RGN) crossbred compared to Nelore (N) cattle, using mRNA analysis of calpain 1 and 2, calpastatin, myostatin, and TGFβ; and protein abundance profile post mortem based on aged beef of the different genetic groups. Sixteen N and 16 RGN were finished in feedlot by 120 days and harvested. RGN beef presented greater tenderness. Transcripts analysis showed increased levels of TGFβ and MSTN in RGN, indicating differences in muscle fiber formation. However, no difference was observed in mRNA for CAPN1, CAPN2 and CAST. Protein analysis demonstrated increased troponin-T degradation in RGN. Interaction for HSP 27 degradation was observed, indicating the degradation of this protein is faster and greater in RGN than N. No difference in myostatin protein abundance was found. In general, RGN cattle improves beef quality and these differences may be explained by TGFβ and MSTN gene expression, troponin-T degradation and HSP abundance.
Keywords: Bos indicus; Bos taurus; HSP and troponin-T; Myostatin; Proteolysis